Molecular probing of low-temperature incommensurate phases: Biological Systems at Low Temperatures - Kikas, J.; Suisalu, A.; Laisaar, A.; Kuznetsov, An. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Two-dimensional (2D) excitation-emission spectra of biphenyl doped with free-base chlorinwere measured at 5 K under various pressures up to 350 MPa. Besides the features related tozero-phonon lines and their phonon sidebands, a broad spectral band amounting to 80% of the totalintensity at 5 K was revealed in the 2D spectra. The obtained inhomogeneous distribution functionshows drastic changes with increasing pressure — the triplet structure observable at normal pressurein the incommensurate phase ICIII of biphenyl converges to a singlet in the high-pressurecommensurate phase CI. These observations are assumed to reflect specific for incommensuratephases relaxation after an optical excitation of probe molecules and interaction of them with theincommensurate modulation wave.